Principles and Norms of State Administrative Law Based on the Creation of Government Instruments - Rizki Tri Saputra; Muhammad Irfan; Farhan Putra Riyanto (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
When we talk about Indonesia as a state of law, we also consider the duties of the government and constitution in terms of the rule of law formed or collected in the Basic Law. But, therefore, the constitution was not implemented effectively enough to address technical issues. Because the state is an organization of power, (HAN) is needed as a tool to supervise the use of state power. The study addresses two issues: the critical limitations of law and regulation. Policies and decisions are based on the principles and standards of HAN and HAN in making laws and regulations, policy rules and decisions. This study is carried out together using a normative legal approach or study. Law Library. According to the results of this study, regulations are essentially abstract or general normative laws that are binding in general (generally applicable) whose task is to regulate things that are essentially general. For the time being, political regulations only function to regulate state affairs and laws and regulations cannot be changed or withdrawn. Finally, Guarantees (Veiligheidsclausule) can shake the basis of legal certainty, so that it can be concluded that it is useless and does not overlap. Such formulations violate the principle of legal certainty on the one hand and the principle of valid presumption on the other.